Inhibiting efferocytosis reverses macrophage-mediated immunosuppression in the leukemia microenvironment - Cruz Cruz, Joselyn; Allison, Kristen C.; Page, Lauren S.; Jenkins, Alexis J.; Wang, Xiaodong; Earp, H. Shelton; Frye, Stephen V.; Graham, Douglas K.; Verneris, Michael R.; Lee-Sherick, Alisa B. (Frontiers in Immunology, 2023)
Previous studies show that the spleen and bone marrow can serve as leukemia microenvironments in which macrophages play a significant role in immune evasion and chemoresistance. We hypothesized that the macrophage driven tolerogenic process of efferocytosis is a major contributor to the immunosuppressive leukemia microenvironment and that this was driven by aberrant phosphatidylserine expression from cell turnover and cell membrane dysregulation. Since MerTK is the prototypic efferocytosis receptor, we assessed whether the MerTK inhibitor MRX2843, which is currently in clinical trials, would reverse immune evasion and enhance immune-mediated clearance of leukemia cells. We found that inhibition of MerTK decreased leukemia-associated macrophage expression of M2 markers PD-L1, PD-L2, Tim-3, CD163 and Arginase-1 compared to vehicle-treated controls. Additionally, MerTK inhibition led to M1 macrophage repolarization including elevated CD86 and HLA-DR expression, and increased production of T cell activating cytokines, including IFN-β, IL-18, and IL-1β through activation of NF-κB. Collectively, this macrophage repolarization had downstream effects on T cells within the leukemia microenvironment, including decreased PD-1+Tim-3+ and LAG3+ checkpoint expression, and increased CD69+CD107a+ expression. These results demonstrate that MerTK inhibition using MRX2843 altered the leukemia microenvironment from tumor-permissive toward immune responsiveness to leukemia and culminated in improved immune-mediated clearance of AML.